Inequality of child mortality among ethnic groups in Sub-Saharan Africa - M Brockerhoff; P Hewett (Bulletin of the World Health Organization, 2000)
Accounts by journalists of wars in several countries of sub-Saharan Africa in the 1990s have raised concern that ethnic cleavages and overlapping religious and racial affiliations may widen the inequalities in health and survival among ethnic groups throughout the region, particularly among children. Paradoxically, there has been no systematic examination of ethnic inequality in child survival chances across countries in the region. This paper uses survey data collected in the 1990s in 11 countries (Central African Republic, Côte d’Ivoire, Ghana, Kenya, Mali, Namibia, Niger, Rwanda, Senegal, Uganda, and Zambia) to examine whether ethnic inequality in child mortality has been present and spreading in sub-Saharan Africa since the 1980s. The focus was on one or two groups in each country which may have experienced distinct child health and survival chances, compared to the rest of the national population, as a result of their geographical location. The factors examined to explain potential child survival inequalities among ethnic groups included residence in the largest city, household economic conditions, educational attainment and nutritional status of the mothers, use of modern maternal and child health services including immunization, and patterns of fertility and migration. The results show remarkable consistency. In all 11 countries there were significant differentials between ethnic groups in the odds of dying during infancy or before the age of 5 years. Multivariate analysis shows that ethnic child mortality differences are closely linked with economic inequality in many countries, and perhaps with differential use of child health services in countries of the Sahel region. Strong and consistent results in this study support placing the notion of ethnicity at the forefront of theories and analyses of child mortality in Africa which incorporate social, and not purely epidemiological, considerations. Moreover, the typical advantage of relatively small, clearly defined ethnic groups, as compared to the majority in the national population, according to fundamental indicators of wellbeing - child survival, education, housing, and so forth - suggests that many countries in sub-Saharan Africa, despite their widespread poverty, are as marked by social inequality as are countries in other regions in the world.